PTU-007 Comparison of Diagnostic Performance Between Two Core Biopsy Needles for Endoscopic Ultrasound-Guided Tissue Acquisition of Solid Pancreatic Lesions. (17th August 2016) - Paranandi, B; Oppong, KW; Dawwas, M; Leeds, JS; Darne, A; Haugk, B; Majumdar, D; Ahmed, MM; Nayar, MK
Abstract : Introduction: A new core biopsy needle (SharkCore) with a novel design has recently been introduced for endoscopic ultrasound guided biopsy. There is as yet no data on how its diagnostic performance compares to the existing core biopsy needle (Procore) in the diagnosis of pancreatic masses. The aim of this study was to compare the diagnostic performance and yield of the two core biopsy needles i.e. the ProCore and the Sharkcore needles in the biopsy of solid pancreatic lesions. This is the first study in literature to compare 2 core biopsy needles. Methods: A retrospective comparison of a prospectively maintained database. Consecutive patients who had EUS guided fine needle biopsy with Procore (100) and Sharkcore (101) were included in the study. Demographic details, site of lesion, number of passes and histological diagnosis. Final diagnosis was based on positive histology or at least 6 months follow up in cases with a benign pathology. Primary outcome was to compare the diagnostic accuracy of the two needles using only samples graded as definitely malignant as diagnostic for malignancy. The secondary outcome was to compare the diagnostic yield for both needles. Results: The sensitivity, specificity, negative predictive value and accuracy between the groups were - Procore =71%, 100%, 28% and 74% vs. Sharkcore =91%, 100%, 53% and 94%. There was a significant difference in sensitivity (p = 0.0003) and accuracy (p = 0.006). The proportion of samples classified as adequate for histological analysis was 87% for Procore and 99% for Sharkcore - this was significantly different (p = 0.0009). There were no complications in either group. Conclusion: In this study the SharkCore biopsy needle demonstrated significantly better diagnostic accuracy and tissue yield. Prospective randomised studies are required. Disclosure of Interest: None Declared